Measles transmission among adults with spread to children during an outbreak: Implications for measles elimination in China, 2014. Issue 51 (12th December 2016) - Ma, Chao; Yan, Shaohong; Su, Qiru; Hao, Lixin; Tang, Shaopei; An, Zhijie; He, Yulong; Fan, Guangfei; Rodewald, Lance; Wang, Huaqing
Highlights: There are few studies that describe adult measles outbreaks in community settings. Virus transmission was initially from adult-to-adult, followed by adult-to-child. Adult susceptibility to measles is a potential threat to measles elimination in China. The importance of targeting susceptible adults during outbreak response immunization is highlighted. Abstract: Introduction: Following implementation of China's 2006–2012 Action Plan for measles elimination, which led to a nadir of measles in 2012, a resurgence started in 2013 that continued into 2014. Measles typically is a disease that mainly affects children. We investigated a community outbreak in 2014 with measles virus transmission among adults without children serving as virus reservoirs. Our investigation highlights adult susceptibility to measles. Methods: We conducted a retrospective active case search, and analyzed confirmed case data to describe person, place, and time characteristics of the outbreak. All individuals with measles with onset during the first 2 months of the outbreak were interviewed face-to-face to determine source(s) of infection and transmission route (from whom and to whom). Results: Among the 280 cases, 220 (77.6%) were among ≥20-year-old adults, 24 (8.6%) were among 8–23 month olds, 22 (7.9%) were among <8-month-old infants, and the remaining 14 (5.9%) were among 2–19 year olds. Of the 83 cases in the early stage of the outbreak, 41 (49.4%) were acquired in the community, 24 (28.9%) were acquired nosocomially, 13 (15.7%) were acquired by family contact, and 5 were imported. Among 44 clearly determined transmission linkages, 37 (84.1%) were adult to other age-group (these include 29 adult-to-adult, seven adult-to-child, and one adult-to-infant), six were from infants to adult and children, and one was child-to-child. Outbreak response immunization activities were implemented by non-selective supplementary immunization activities, with 51.3% of targeted 5–19-year-old children and adolescents, and 30.2% of targeted 20–49-year-old adults being vaccinated. Conclusions: Despite high population immunity among children and adolescents following three rounds of measles vaccine supplementary immunization activities, sustained measles virus transmission still occurred among adults in this community. Adult measles immunity gaps might threaten measles elimination, highlighting the importance targeting susceptible adults during outbreak response immunization.